Identification of a c.544C>T mutation in WDR34 as a deleterious recessive allele of short rib-polydactyly syndrome - Shu-Han You; Yun-Shien Lee; Chueh-Pai Lee; Chih-Peng Lin; Chiao-Yun Lin; Chia-Lung Tsai; Yao-Lung Chang; Po-Jen Cheng; Tzu-Hao Wang; Shuenn-Dyh Chang (Elsevier, 2017)
Objective: Single-nucleotide polymorphism (SNP) microarrays and whole-exome sequencing (WES) are tools to precisely diagnose rare autosomal recessive (AR) diseases. In this study, SNP chip and WES were used to identify a mutated location in WDR34 in a baby born to consanguineous parents. Case report: The baby, born at 36 gestational weeks had a small thoracic cage, symmetric short proximal bones, and polydactyly. Radiography showed short ribs with reduced lung volume and pulmonary opacities, compatible with asphyxiating thoracic dystrophy or short rib-polydactyly syndrome (SRPS). At 4 months of age, she died of pulmonary hypoplasia and sepsis. SNP microarray and evaluation tool confirmed WDR34 as the candidate gene. WES detected an AR mutation at c.554C > T [p.Arg182Trp] in WDR34. Conclusion: This study was the first to identify c.544C > T [p.Arg182Trp] mutation in WDR34 in a patient with SRPS. According to the database, the homozygous mutation of c.544C > T in WDR34 was deleterious and the prevalence of heterozygous mutation was relatively higher in Asian population. More studies of this mutation in patients with SRPS are required.